Loss of spinal substance P pain transmission under the condition of LPA1 receptor-mediated neuropathic pain - Chun Jerold; Kawakami Megumi; Yamaguchi Asuka; Inoue Makoto; Ueda Hiroshi (SAGE Publishing, 2006)
Abstract Among various machineries occurring in the experimental neuropathic pain model, there exists the loss of pain transmission through C-fiber neurons as well as the hypersensitivity through A-fibers. The current study reveals that molecular machineries underlying the latter hypersensitivity are derived from the events through LPA1 receptor and its downstream RhoA-activation following peripheral nerve injury. The loss of C-fiber responses, which are mediated by spinal substance P (SP) pain transmission was observed with the nociceptive flexor responses by intraplantar injection of SP in nerve-injured mice. The immunohistochemistry revealed that SP signal in the dorsal horn was markedly reduced in such mice. All these changes were completely abolished in LPA1-/- mice or by the pretreatment with BoNT/C3, a RhoA inhibitor. In addition, the loss of C-fiber responses and the down-regulation of spinal SP signal induced by single intrathecal LPA injection were also abolished in such treatments. All these results suggest that the loss of pain transmission through polymodal C-fiber neurons is also mediated by the LPA1 activation following nerve injury.